Challenges in implementing engineering technology education in Malaysia - Ali, Rosmah (2015)
As Malaysia races against time to achieve Vision 2020 to be a developed nation, there is an urgent need for highly-skilled human resources to fulfill the requirements of the industry. This calls for an expansion of the engineering technology program to increase the number of technical graduates. However, various challenges are faced by the institutions in the implementation of the Engineering Technology programs, which have significant negative impact on the nation in general and in particular the graduates from the programs. Data was collected from a brainstorming session between six organizations involved in providing engineering technology education in Malaysia and the UniversitiTeknologi Malaysia (UTM) and a convention on Engineering Technology Future in Malaysia. These challenges are categorized into four and discussed in this paper.